Molecular characterization of p38 MAPK from blunt snout bream (Megalobrama amblycephala) and its expression after ammonia stress, and lipopolysaccharide and bacterial challenge. Issue 84 (January 2019) - Zhang, Chun-Nuan; Rahimnejad, Samad; Lu, Kang-Le; Zhou, Wen-Hao; Zhang, Ji-Liang
Abstract: p38 mitogen-activated protein kinase (MAPK) is an important protein which plays a key role in regulating the innate immunity, so exploring its molecular characterization is helpful in understanding the resistance against microbial infections in cultured fish. Here, a full-length cDNA of p38 MAPK was cloned from liver of blunt snout bream ( Megalobrama amblycephala ) which covered 2419 bp with an open reading frame of 1086 bp encoding 361 amino acids. p38 MAPK contained the characteristic structures of Thr-Gly-Tyr (TGY) motif and substrate binding site Ala-Thr-Arg-Trp (ATRW), which are conserved in MAPK family. To investigate p38 MAPK functions, two in vivo experiments were carried out to examine its expression following ammonia exposure and bacterial challenge. Also, an in vitro experiment was conducted to assess the role of p38 MAPK in inflammation of primary hepatocytes induced by lipopolysaccharide (LPS). The results showed the ubiquitous expression of p38 MAPK in all the tested tissues with varying levels. p38 MAPK mRNA expression was significantly up-regulated by ammonia stress and Aeromonas hydrophila challenge, and altered in a time-dependent manner. Moreover, the results indicated that the inflammatory response induced by LPS in hepatocytes is p38 MAPK dependent as knockdown of p38 MAPK using siRNA technology depressed the expression of IL-1β and IL-6. The findings in this study showed that p38 MAPK has anti-stress property, and plays key role in protection against bacterial infection and inflammation in blunt snout bream. Highlights: p38 MAPK was characterized in blunt snout bream. p38 MAPK expression was explored after ammonia stress and bacterial challenge. p38 MAPK role was tested in inflammation of primary hepatocytes. p38 MAPK was up-regulated by ammonia stress and A. hydrophila challenge. Knockdown of p38 MAPK using siRNA lowered the inflammatory response.